CORRELATION AND DIVERSITY OF SIZE OF MOVEMENT TOOLS AND BODY HEIGHT OF ETAWA CROSSBREED GOATS IN UMEJERO VILLAGE, BUSUNGBIU DISTRICT, BULELENG, BALI - Muh Adnan Ghafur Hamzah; I Putu Sampurna; Wayan Bebas (Buletin Veteriner Udayana, 2025)
Etawa crossbred goats are goats that are the result of crossbreeding between Kacang goats and Etawa goats. This study aims to determine the correlation and diversity of locomotor size and body height of Etawa crossbred goats (PE) in Umejero Village, Busungbiu District, Buleleng, Bali. A total of 81 PE goats consisting of 44 male PE goats and 37 female PE goats were used in this study. The variables observed were the length of the upper front leg, the length of the middle front leg, the length of the lower front leg, the length of the upper hind leg, the length of the middle hind leg, the length of the lower hind leg, shoulder height, and hip height. The data obtained were analyzed using biplot analysis. The results showed that there was a positive correlation between hip height and the length of the upper, middle, and lower hind legs. Shoulder height was also positively correlated with the length of the upper, middle, and lower front legs. There was no significant difference in diversity (P>0.05) between the size of the locomotor and the height of PE goats. PE goats in quadrant I on the biplot graph have above average body size and have the potential to be used as seeds or fattened. PE goats in quadrant III have below average body size and are not good for use as seeds or fattened. Shoulder height and hip height are the most important variables to measure in the selection of PE goats in Umejero village. It is recommended to select breeding stock with a minimum standard of 70.6 cm shoulder height and 84.2 cm hip height in order to obtain livestock with above average growth performance.